Escritura adolescente: una revisión basada en resultados de investigación recientes - Amaya Pisco, Jorge Orlando (Colombian Applied Linguistics Journal, 2011)
This research aims to critically look at some recent studies on young people’s writing. It is made up of three parts: the first one points out some researches associated with university people’s writing in the freshmen year. The second one contains reports which focus on the writing of students in Hihgh school and the third one refers to an investigative panorama on the extra-curricular writing or writing directly or indirectly dissociated from an educational environment. The search provides two findings: In the first, the fact that the recent investigations about the elaborate writing by adolescents tends to go towards the qualification of metacognitive processes; the second one shows the absence of alternative writings different from those proposed by the school or university. These are normally considered as or unnecessary unimportant activities.